"A new physical aspect for elastic-viscous transition and velocity jump in fracture of rubbers". (8th September 2017) - Fukahori, Y.; Sakulkaew, K.; Busfield, J.J.C.
Abstract: The elastic-viscous transition of tear fracture of rubber consists of three different fracture zones, the elastic-brittle fracture zone, the viscous-ductile fracture zone and the intermediate transition zone accompanied with stick-slip motion and a corresponding velocity jump at a constant strain energy release rate. Following the previous paper where the fundamental concept named the elastic-viscous transition for the velocity jump was newly introduced, here in addition the authors propose another new physical concept for the mechanism of the elastic-viscous transition in comparison with the phase transition of water. The vibrational energy caused by the stick-slip motion converted from the external strain energy works as a driving force for the velocity jump, being similar to the situation when the latent heat converted from an external heating source causes a volume jump in the phase transition of water. The greatly increased vibrational energy might be consumed to accelerate the ductile fracture of the newly induced fraction of the glassy state in the transition process from the rubbery to glassy state around the glass transition region, resulting in the velocity jump at the elastic-viscous transition. It is the purpose of this paper to answer the essential question why the abrupt and significant velocity change occurs under circumstances where the input strain energy release rate is kept constant. Graphical abstract: This figure shows the frequency f of vibration generated during tear fracture of rubber against the crack growth rate G ˙ over three different fracture zones, where in the transitionⅡ f increases proportionally with G ˙, meaning that the vibration energy converted from the external strain energy works as a driving force for the accelerated crack propagation, thus causes the velocity jump in the transition zoneⅡ. Highlights: The physical meaning of the elastic-viscous transition accompanied with velocity jump in fracture of rubber is made clear. The vibrational energy inserted by stick-slip motion generates the velocity jump in the transition zone. The vibrational energy converted from the external strain energy works as a driving force for the rapid crack growth. This is just the velocity jump in the transition zone of the elastic-viscous transition phenomenon. This phenomenon is quite similar a volume jump in the phase transition of water.